Determination of the Differential Equations of a Dynamical System using Dual Description - Rónai, László (International Journal of Engineering and Management Sciences, 2024)
The paper deals with the description of a mathematical model of a mechanical system using the so-called energy-based approach. The model is created using both generalized displacements and generalized momenta. The latter prescription method is less common in practice, due to its complexity. The two ways are presented through the same example mechanical problem, and a control task is also solved with the help of a PID block.